Aging of the society: the European perspective - Kiniorska, Iwona; Brambert, Patryk; Kamińska, Wioletta; Kopacz-Wyrwał, Iwona (Bulletin of Geography. Socio-economic Series, 2023)
Population aging is a key risk for the future of Europe. Th e Old Continent has to face ever-stronger new demographic trends and fi nd eff ective strategies to address them. In this study, we evaluate the progress of population aging in Europe in the period of 2008–2021. Th e broad time span of our considerations concerns the years 1960–2100. We present our new typological approach to the areas of unbalanced age structure. Its classifi cation includes four groups of countries with various distribution of aging measures, i.e., the percentage of people aged 65 and over and the dynamics of its growth. We observe that the largest group is composed of countries exceeding arithmetic means for both above-mentioned aging measures, which are located mainly in Eastern and Southern Europe. According to stages of aging by median age, most of these countries reached the stage of very old population in the 1990s